`f''(x) = 20x^3 - 12x^2 + 6x` Find `f`.

Expert Answers

An illustration of the letter 'A' in a speech bubbles

`f''(x)=20x^3-12x^2+6x`

`f'(x)=int(20x^3-12x^2+6x)dx`

Applying the sum rule and power yields,

`f'(x)=20(x^4/4)-12x^3/3+6x^2/2+c_1`

`f'(x)=5x^4-4x^3+3x^2+c_1`

`f(x)=intf'(x)dx`

`f(x)=int(5x^4-4x^3+3x^2+c_1)dx`

`f(x)=5(x^5/5)-4(x^4/4)+3(x^3/3)+c_1x+c_2`

where c_1 and c_2 are constants, simplifying the above

`f(x)=x^5-x^4+x^3+c_1x+c_2`

Unlock
This Answer Now

Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Start your 48-Hour Free Trial

`f''(x)=20x^3-12x^2+6x`

`f'(x)=int(20x^3-12x^2+6x)dx`

Applying the sum rule and power yields,

`f'(x)=20(x^4/4)-12x^3/3+6x^2/2+c_1`

`f'(x)=5x^4-4x^3+3x^2+c_1`

`f(x)=intf'(x)dx`

`f(x)=int(5x^4-4x^3+3x^2+c_1)dx`

`f(x)=5(x^5/5)-4(x^4/4)+3(x^3/3)+c_1x+c_2`

where c_1 and c_2 are constants, simplifying the above

`f(x)=x^5-x^4+x^3+c_1x+c_2`

Approved by eNotes Editorial Team